Outlander. Season five [videorecording (DVD)] - Moore, Ronald D. (Sony Pictures Home Entertainment, 2020)
The fifth season of Outlander sees a continuation of Claire and Jamie's fight to protect those they love, as they navigate the trials and tribulations of life in colonial America. The Frasers strive to flourish within a society which is unwittingly marching towards Revolution, and Jamie must now defend the home they have built together at Fraser's Ridge while Claire seeks to put her own skills and medical expertise to use in keeping her family together and safe from harm. Meanwhile, Brianna and Roger MacKenzie struggle to find their respective places in this world and chase away the shadow cast over their lives by Stephen Bonnet as they raise their son in this brave new world. For the Frasers and their family, "home" is more than simply a site in which they live, it is the place in which they are laying the foundations for the rest of their lives...